The Christ’s and the Christian Faith’s Civic Thought - Molteni-Eli, Agostino; Solís-Nova, David (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
In this article we want to highlight, as a first point, the civic thought of Christ that is based on Trinitarian logic and that is continued earthly in the way in which he thinks about his incarnation and the redemption of men. Second, some reflections are proposed on the civic nature of the Christian faith, which is the legitimate heir to the thought of Christ. Both reflections are elaborated methodologically from within the civic thought of Christ and from within the co-institution of the Christian as his fellow citizen in the civitas founded by him in history.